PENGARUH MANAJEMEN LABA, KUALITAS AUDITOR, DAN KESULITAN KEUANGAN PADA KETEPATAN WAKTU PELAPORAN KEUANGAN - Seni, Ni Nyoman Anggar; Mertha, I Made (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
This study aims to know the effect of earnings manipulation, quality auditors, and financial distress on the timeliness of financial reporting manufacturing companies located in Indonesia Stock Exchange 2010-2012. The number of companies studied were 37 company for 3 years, so the number of samples were 111 companies. The sample selected based on specific criteria. Using a binary logistic analysis. Results of analysis showed that earnings manipulation , quality auditors, and liquidity as a proxy for financial distress affect the timeliness of financial reporting manufacturing company. However, leverage as a proxy for financial distress had no affect on the timeliness of financial reporting manufacturing company.
Keywords: timeliness,earnings manipulation,quality auditors,financial distress